Evolution Architectural Heritage Through Typology Of Negeri Sembilan Traditional Houses - Surat, Mastor; Ismail, Noor Hayati; Raja Shahminan, Raja Nafida; Yunus, Shahrul Kamil (Universiti Sains Malaysia, 2016)

(untitled)
The architecture of traditional house is a regional architectural heritage assets which are valuable, inherited and built in various customs and cultures of each country. It has the characteristics of the different designs and concepts that shape its own identity. The uniqueness design of the Negeri Sembilan traditional house is influenced by the Minangkabau, West Sumatra, Indonesia, which is the symbol of the community. Minangkabau house is a house occupied by the customary rules of practice matrilineal kinship system and the tendency of the people to go abroad for the purpose of exploration. The study was made on the basis of these factors, the occurrence of evolution, the changes that occurred since the 14th century AD, which started from Minangkabau to Negeri Sembilan, Malaysia. Additionally, the study proves that the customs, culture and regionalism have established the typology of Negeri Sembilan traditional houses. The study involves several locations starting from West Sumatra, Indonesia such as Padang, Bukit Tinggi and Kampar to Negeri Sembilan, Malaysia such as Rembau, Tampin and Kuala Pilah. The data were obtained through a process of observation, sketches, interviews, questionnaires and related photos. The identity and uniqueness of Negeri Sembilan traditional house is the architectural heritage that will bring awareness and references to future generations which are increasingly difficult to sustain and lost in their own country